Respuesta :

 i think it' =-8abc(a+b-c)

The result of the product is a + 4b

The expression is given as:

  • [tex]-a +2b + 2c +2(a + b - c)[/tex]

Open the brackets

[tex]-a +2b + 2c +2(a + b - c) = -a +2b + 2c +2a + 2b - 2c[/tex]

Collect like terms

[tex]-a +2b + 2c +2(a + b - c) = -a +2a+2b + 2b + 2c - 2c[/tex]

Evaluate the like terms

[tex]-a +2b + 2c +2(a + b - c) = a+4b[/tex]

Hence, the result of the product is a + 4b

Read more about expressions at:

https://brainly.com/question/13729904

ACCESS MORE